Abnormal Expression of ERα in Cholangiocytes of Patients With Primary Biliary Cholangitis Mediated Intrahepatic Bile Duct Inflammation - Hui Cao; Bukun Zhu; Yao Qu; Wei Zhang (Frontiers in Immunology, 2019)
ERα, one of the classical receptors of estrogen, has been found to be abnormally up-regulated in patients with primary biliary cholangitis (PBC), which is an important factor leading to ductopenia. ERα-mediated signaling pathways are involved in proliferation of human intrahepatic biliary epithelial cells (HiBECs) and portal inflammation. Our previous studies have shown that the expression levels of ERα in the liver tissues of PBC patients are positively correlated with the levels of serum pro-inflammatory cytokines. The present study was designed to assess the relationship between abnormal ERα expression in small bile ducts and the progression of PBC. We examined the levels of multiple cytokines and analyzed their relationship with clinical parameters of livers functions in a cohort of 43 PBC patients and 45 healthy controls (HC). The levels of ERα expression and the relation with the levels of cytokines were further assessed. The localization of cytokines and ERα-mediated signaling pathways in liver were examined using immunohistochemistry. The possible underlying mechanisms of these alterations in PBC were explored in vitro. Our results demonstrated that the levels of IL-6, IL-8, and TNF-α were increased in PBC patients, and positively correlated with the serum AKP levels and ERα expression levels. Moreover, the expression of these cytokines were up-regulated in HiBECs that were stimulated with 17β-estradiol and PPT (an ERα agonist) and they also were positive in intrahepatic bile duct of PBC patients. The ERα-mediated expression of pro-inflammatory cytokines was induced by JNK, P38, and STAT3 phosphorylation in HiBECs. In addition, the CD54 expression was increased in HiBECs after ERα activation, which induced peripheral blood monouclear cells (PBMCs) recruitment. In conclusion, the present study highlighted a key role of abnormal ERα expression in inducing an inflammatory phenotype of HiBECs, which was critical in the development of inflammation and damage in small bile duct.